2010
DOI: 10.1152/ajpgi.00264.2009
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of angiotensin II type 1 receptor regulates TNF-α-induced MAdCAM-1 expression via inhibition of NF-κB translocation to the nucleus and ameliorates colitis

Abstract: Mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) is an important target in the treatment of inflammatory bowel disease (IBD). Recently, treatment of IBD with an antibody to alpha4beta7-integrin, a ligand for MAdCAM-1, has been an intense focus of research. Our aim was to clarify the mechanism by which MAdCAM-1 is regulated via angiotensin II type 1 receptor (AT1R), and to verify if AT1R might be a novel target for IBD treatment. The role of AT1R in the expression of MAdCAM-1 in SVEC (a murine hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 53 publications
2
55
1
Order By: Relevance
“…RAS has been implicated in the pathogenesis of IBD via upregulation of Ang II AT1 receptors throughout the colon [1], [8]. Ang II is involved in several key steps of the inflammatory cascade that ultimately provoke intestinal injury and ulceration including polymorphonuclear leukocyte (PMN) infiltration, probably, via upregulation of adhesion molecules [8], [42].…”
Section: Discussionmentioning
confidence: 99%
“…RAS has been implicated in the pathogenesis of IBD via upregulation of Ang II AT1 receptors throughout the colon [1], [8]. Ang II is involved in several key steps of the inflammatory cascade that ultimately provoke intestinal injury and ulceration including polymorphonuclear leukocyte (PMN) infiltration, probably, via upregulation of adhesion molecules [8], [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the renin-angiotensin system was reported to be involved in the pathophysiology of colitis, suggesting that antagonism of the renin-angiotensin system such as angiotensin II receptor may be a potential prophylactic strategy for the treatment of human IBD [74,75]. In fact, angiotensin receptor antagonist is effective in preventing experimental colitis through the blockade of growth factor-beta1 overexpression or via regulation of mucosal vascular addressin cell adhesion molecule 1 [76][77][78][79]. Therefore, considering the fact that telmisartan has its function as an angiotensin II type 1 receptor blocker and a PPAR-g agonist, we cannot rule out the possibility that telmisartan showed its ability in attenuation colon inflammation through regulation of renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…Mizushima et al (43) reported that AT 1 R regulates the expression of mucosal addressin cell adhesion molecule-1 under colonic inflammatory conditions through regulation of the translocation of NF-B into the nucleus. Furthermore, they demonstrated that inhibition of the AT 1 R ameliorated colitis in a mouse colitis model (43).…”
Section: Discussionmentioning
confidence: 99%